2013
DOI: 10.20873/jbb.uft.cemaf.v4n2.ootani
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de Óleos Essenciais na Agricultura

Abstract: Essential oils are alternative to control pathogenic agents, agricultural pests and weeds, with the use of pesticides in agriculture has been an important tool in the control of many pathogenic microorganisms and plants to increase production, but the indiscriminate use of these chemicals has negatively affected the environment and human health. It has been researched lately, demand for new plants with metabolic molecules such as terpenes, alkaloids and phenolic compounds, in effect; bioinsecticide, biofungici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 76 publications
1
6
0
12
Order By: Relevance
“…The study by the authors of [10] also reported a significant concentration of monoterpenes, such as pinenes occuring in greater quantity, in addition to sesquiterpenes and eudesmol isomers. According to the author, this characteristic is frequent in essential oils collected from Brazil, these being commercially important volatile compounds [25]. The authors of [26] studied the chemical composition of essential oils from the Calyptranthes genus and identified a high concentration of cyclic sesquiterpenes such as Caryophyllene, Germacran and Cadinanol, in accordance with the present study, which are considered common compounds in Myrtaceae.…”
Section: Discussionsupporting
confidence: 86%
“…The study by the authors of [10] also reported a significant concentration of monoterpenes, such as pinenes occuring in greater quantity, in addition to sesquiterpenes and eudesmol isomers. According to the author, this characteristic is frequent in essential oils collected from Brazil, these being commercially important volatile compounds [25]. The authors of [26] studied the chemical composition of essential oils from the Calyptranthes genus and identified a high concentration of cyclic sesquiterpenes such as Caryophyllene, Germacran and Cadinanol, in accordance with the present study, which are considered common compounds in Myrtaceae.…”
Section: Discussionsupporting
confidence: 86%
“…The results presented here shows the importance of plant extracts and derivatives as sources of efficient bioactive compounds in the management of plant diseases through direct effect on pathogens or as potential sources of a new defense response elicitors and as an alternative to chemical control, which have been indiscriminately used. According to Ootani (2013) exploration of the biological activity of secondary compounds present in the crude extract or essential oil of medicinal plants can be, with resistant induction, another potential alternative form of disease control in cultivated plants.…”
Section: Resultsmentioning
confidence: 99%
“…Os óleos essenciais são substâncias naturais voláteis de composição complexa, aromatizantes, lipofílicos de baixo peso molecular, constituídos principalmente fenilpropanóides e terpenóides. Podem ser encontrados em diferentes partes das plantas como folhas, raízes, flores, frutos, casca de caule e podem ser armazenados em tricomas glandulares, canais oleíferos, células epidérmicas, bolsas lisígenas ou células parenquimáticas diferenciadas (OOTANI et al, 2013). O uso desses produtos na agricultura, está relacionado ao seu potencial antifúngico, inibindo o crescimento micelial e germinação de esporos.…”
Section: Introductionunclassified